Pemanfaatan Media Sosial Instagram Bisnis Terhadap Peningkatan Omzet Penjualan Produk “Fanaya Catering” - Nurkhayati Nurkhayati; Toto Sudibyo; Moh. Miftah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
One of the digital media frequently used by business practitioners for promotion is Instagram. Instagram is utilized as a promotional medium due to its more appealing interface compared to Facebook or Twitter. Instagram is an application for capturing, editing, and sharing photos within the Instagram user community. The research was conducted using a descriptive quantitative approach. Research data was collected through a questionnaire distributed randomly to 99 respondents who were followers of the